Case Report: Primary Extraskeletal Osteosarcoma in the Lung and Pulmonary Artery - Zhai, Duchang; Cai, Wu; Fan, Guohua; Yang, Junlin; Liu, Chenchen (Frontiers in Oncology, 2021)
Extraskeletal osteosarcoma is an uncommon and high-grade soft tissue malignancy. The incidence is even lower when the lung and pulmonary artery are the primary site. The purpose of this report is to present the radiological features of this neoplasm in a 52-year-old man. In our case, contrast-enhanced CT and 3D-CT reconstruction clearly showed the primary lesion and its invasion into surrounding tissues. Although wide local excision of the primary tumor is the treatment of choice, local recurrence and metastasis rates remain high, and this progression can be clearly shown on CT and SPECT/CT examinations.